Ischemic Stroke in Patients Under Oral Anticoagulation: The Achilles Heel of Atrial Fibrillation Management - Kyriakos Dimitriadis; Nikolaos Pyrpyris; Konstantinos Aznaouridis; Gyanaranjan Nayak; Panagiotis Kanatas; Panagiotis Theofilis; Panagiotis Tsioufis; Eirini Beneki; Aggelos Papanikolaou; Christos Fragoulis; Konstantina Aggeli; Konstantinos Tsioufis (Brain Sciences)
Oral anticoagulation (OAC) is essential for preventing ischemic stroke events in patients with atrial fibrillation (AF), and leads to a significant ischemic prophylaxis, when appropriately used. However, there is still a risk of experiencing stroke events, despite being under anticoagulation. Stroke despite OAC is an increasingly common diagnosis, and pathophysiologically, it can be associated with several etiologies, ranging from AF competing mechanisms to true anticoagulation failure. While the cardioembolic origin of stroke is the most frequently identified etiology, other factors also have to be considered, as there is a significance risk of coexistence. This highlights the need for thorough diagnostic testing, evaluating each stroke etiology independently, with the use of imaging, biomarker and blood tests. Treating such patients, however, is more complex, as there is still uncertainty regarding the selection of OAC post-stroke, with data showing a superiority of direct OAC (DOAC), compared to vitamin K antagonists, in recurrent ischemic stroke prevention and conflicting results regarding OAC switch. Finally, the additive value of cardiac interventions, such as left atrial appendage occlusion (LAAO), in secondary prevention of stroke, is being explored, as it could potentially lead to significant stroke risk reduction. This review, therefore, provides an updated summary of the pathophysiology, diagnostics and therapeutics of stroke under OAC, while also discussing the future direction on the Achilles heel of AF management.